МАРШРУТ ПОЭТА: НЬЮ-ЙОРК В ПОЭЗИИ Д. БУРЛЮКА (Filološke studije, 2019)
The paper deals with an American period of well-known Russian futurist poet D. Burliuk (1920th-1930th). Burliuk was one of the most prominent poets of Russian émigré literature of the first three decades of the 20th c. It was he, who took part in forming of “New York text” of Russian émigré literature. The process of learning of the new world by Russian immigrants was embodied in his poetry of that time, which can be considered as an attempt to assimilate the new world and to become more familiar with one. The Urbanistic poetics of Burliuk`s texts correspondences with dramatic experience of the protagonist the most completely. In most texts by Burliuk the American world has been shown as alien for the protagonist. Folloing the futurist poetics Burliuk depicts disharmonious space, broken proportions, embodying the disharmony both social and personal life. In numerous texts there is constructed the opposition Homeland (wide, horizontal space) – New York, de-esthetic, stony, disproportional, clutched city. Poems, where the image of New York is constructed, seems to forestall famous American cycle by Mayakovski. However there is one remarkable difference between them: Burliyuk`s texts realize the inside-situation and point of view, whereas view of Mayakovski is a view outside, his outlook is a glimpse of observer.